Squaramide-catalyzed asymmetric Mannich reactions between 3-fluorooxindoles and pyrazolinone ketimines - Zhang, Qing-Da; Zhao, Bo-Liang; Li, Bing-Yu; Du, Da-Ming (Organic & biomolecular chemistry, 2019)
An enantioselective Mannich reaction between 3-fluorooxindoles and pyrazolinone ketimines has been developed for the construction of amino-pyrazolone-oxindoles containing stereogenic C-F units. Based on this new protocol that allows for the generation of two adjacent tetrasubstituted stereocenters, a variety of structurally diverse fluorinated amino-pyrazolone-oxindoles were obtained in good to excellent yields with excellent diastereoselectivities and enantioselectivities (up to 98% yield, >20 : 1 dr and >99% ee). What's more, good yield and high stereoselectivities were obtained in the gram-scale reaction. Squaramide-catalyzed asymmetric Mannich reaction between 3-fluorooxindoles and pyrazolinone ketimines afforded fluorinated amino-pyrazolone-oxindoles with two quaternary stereocenters in good to excellent yields with excellent stereoselectivities.